Estimativa da correção do coeficiente de retorno de esgoto sanitário em habitações com sistemas de aproveitamento de água pluvial: estudo de caso da cidade de Bauru (SP) - Leão, Cintia Loturco Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Several studies have been conducted proposing water conservation techniques to minimize the treated water consumption. Among them stands out the rainwater utilization in activities that may dispense the potability. In Brazil, the pricing on the collection and treatment services of sewage, is generally performed based on the volume of treated water measured at the meter of the consumer unit. Therefore, this sewage disposal generated by rainwater utilization system is not accounted for sewage charging system on the cost of disposal and treatment. The use of this rainwater underestimates the volume of sewage generated. This paper proposes the application of the methodology for setting this return coefficient to estimate the volume of rainwater released in the sewage disposal system linked to the volume of treated water measured at the meter of each consumer unit. The sanitary bowl with box attached was adopted as an object of study. From the collection of roof areas sampling the city of Bauru (SP) determined the average area of the roof. Different simulations of determining roof areas, reservoir volumes and water consumption demands were made, in order to analyze the return coefficient setting behavior for the average area of roof per capita (m2.hab-1). The results showed that the city of Bauru (SP) features a roof area of approximately 139.91 = 3.12 m2 for homes, 5.58 m2.hab-1 for apartments and wa weighted average area of 132.18 m2 per household. With an average are per capita of 49,21 m2. It was found that in all per capita consumpetion ranges, for volume of 0.5 m3 reservoir/in habitant, the release of rainwater in the sewage disposal system was efficient with values less than 30% specific coverage areas 4-17 m2.hab-1 therefore concluded that discharges into sanitary bowl were not met fully by rainwater utilization system. In this way it was stated that not all use of water for unloading in sanitary bowl is transferred to the collection...

Vário estudos têm sido realizados propondo técnicas de conservação de água, visando minimizar o consumo de água tratada. Dentre eles destaca-se o aproveitamento de água pluvial em atividades que possam prescindir da potabilidade. No Brasil, a cobrança dos serviços de coleta e tratamento de esgoto sanitário, em geral, é realizada com base no volume de água tratada medida do hidrômetro da unidade consumidora. Portanto, esse descarte de esgoto gerado pelo sistema de aproveitamento de água pluvial não é contabilizado pelo sistema de tarifação de esgoto no custo de destinação e tratamento. A utilização dessa água pluvial subestima o volume de esgoto gerado. Este trabalho propõe a aplicação da metodologia para o ajuste desse coeficiente de retorno visando estimar o volume de água pluvial lançado na rede coletora de esgoto indexado ao volume de água tratada medido no hidrômetro de cada unidade consumidora. A bacia sanitária com caixa acoplada foi adotada como objeto de estudo. A partir da coleta de amostragens de áreas de telhado do município de Bauru (SP), determinou-se a área média de telhado. Diferentes simulações de determinação de áreas de telhado, volumes de reservatórios e demandas de consumo de água foram realizadas, com o intuito de analisar o comportamento do ajuste do coeficiente de retorno para a área média de telhado per capita (m2.hab-1). Os resultados apontaram que o município de Bauru (SP) apresent uma área de telhado da ordem de 139,91 = 3,12m2 para residências, de 5,58 m2.hab-1 para apartamentos e uma área média ponderada de 132,18 m2 por domicílio. Apresentando uma área média per capita de 49,21 m2. Verificou-se que em todas as faixas de consumo per capita, para o volume de reservatório de 0,5 m3.hab-1, o lançamento de água pluvial na rede coletora de esgoto apresentou eficiência com valores menores que 30% para as áreas específicas de cobertura de 4 a 17 m2.hab-1, portanto...
Keywords: Agua - Reutilização; Eficiência do uso da água; Agua - Conservação; Aguas pluviais - São Paulo (Estado); Water reuse